ANALISIS KINERJA BADAN PERMUSYAWARATAN DESA SENDAWAR DALAM PENYUSUNAN PERATURAN DESA KECAMATAN SEMIDANG ALAS MARAS KABUPATEN SELUMA - Ardiyansyah, M. Abdul Rikdan; Adriadi, Rekho (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
The Village Consultative Body (BPD) has an important role in drafting village regulations. The Village Consultative Body discusses and approves draft village regulations proposed by the village head, and supervises their implementation. They also collect input from residents and ensure village regulations meet community needs. The preparation of village regulations is the process of forming rules that apply at the village level, aimed at regulating the lives of village communities and the administration of village government. The aim of this research is to determine the performance of the Sendawar Village Consultative Body in drafting village regulations in Semidang Alas Maras District, Seluma Regency. The type of research used in this research is qualitative with a descriptive approach. The unit of analysis in this study consisted of 8 (eight) informants chosen deliberately who were considered to know best what the researcher expected. Data collection techniques include observation, interviews and documentation. The results of this research state that the performance of the Sendawar Village Consultative Body, Semidang Alas Maras District, Seluma Regency has not gone well. This is because in this village there are no village regulations prepared by the Village Consultative Body and Village Government. The absence of village regulations results in a lack of guidelines for regulating village social, economic and environmental life, which can trigger conflicts between residents and slow down village development. Apart from that, legal uncertainty can also reduce public trust in village government. This also indicates that the function of the Sendawar Village Consultative Body in discussing and approving village regulations is not running well or is not optimal. Keywords: Village Consultative Body, Performance, Village Regulations